German Ambassadors visit to UMP strengthens bilateral good relations - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PEKAN, 26 January, 2022 - The visit by the German Ambassador to Malaysia, TYT Dr. Peter Blomeyer to Universiti Malaysia Pahang (UMP) strengthened the 12 years of academic collaboration between Universiti Malaysia Pahang (UMP) and German educational institutions in developing the German engineering education model (Fachhochschule) in the country’s technical education system.